2021
DOI: 10.1111/edt.12708
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of information on YouTube™ regarding pediatric dental trauma

Abstract: Background/Aim Traumatic dental injuries are a common health problem in children. The aim of this study was to evaluate the quality of the video contents on YouTube™ regarding traumatic dental injuries in children taking into account the information of IADT, and to analyze whether it is useful for patients and dentists. Material and Methods A search was performed on YouTube™ using the search term “trauma in pediatric dentistry” with the default filter set to “sort by relevance”. Based on this search, 127 video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
2
12
1
6
Order By: Relevance
“…These findings are inconsistent with some previously published studies [11,13,18,25,28,29]. However, other studies indicated that videos with high usefulness scores were longer [20][21][22][23]. In this study, no significant differences were found in video demographics among the different authorship sources except for video duration where academic institutions uploaded longer videos which also gave better usefulness scores.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are inconsistent with some previously published studies [11,13,18,25,28,29]. However, other studies indicated that videos with high usefulness scores were longer [20][21][22][23]. In this study, no significant differences were found in video demographics among the different authorship sources except for video duration where academic institutions uploaded longer videos which also gave better usefulness scores.…”
Section: Discussioncontrasting
confidence: 99%
“…Past experiments have studied the YouTube videos contents for various oral-health-related topics [15,[17][18][19][20][21][22][23][24][25]. In the present study, the video content was evaluated based on the AAE guidelines regarding periradicular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Around 80% of the evaluated videos were uploaded by health care professionals. Consistently, previous studies showed that YouTube videos for different oral-health-related topics are mostly uploaded by healthcare professionals, compared with other sources of upload [ 34 38 ]. However, there is a need for further improvement of the videos uploaded by academic institutions as only a few of them sufficiently mentioned all the needed details to produce an inclusive educational video needed for the purpose of adequate learning by the students.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, it is necessary to evaluate the videos uploaded to YouTube. As a result, several studies on dentistry, such as bleaching, dental trauma, early childhood caries, clear orthodontic aligners, and cleft lip, have been conducted on YouTube [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%